INFLATION IN NIGERIA AND THE IMPORTANCE OF MONETARIST SCHOOL: A CONCEPTUAL REVIEW ON CURRENCY REDENOMINATION - Apere, ThankGod Oyinpreye; Uche, Warlice Joel (EBSU Journal of Social Sciences and Humanities, 2024)
Redenomination generally has good effects on the nation's economy and is symbolic. This study's objective is to theoretically explore currency redenomination as a monetary tactic for boosting the economy in the face of inflation. According to monetary theory, changes in the money supply, such as increases or reductions, are the most typical reason for economic fluctuations within a particular system, such as shifting inflation rates. In light of the rising cost of living and the naira's depreciation against other currencies, this paper concludes that redenomination as a monetary policy is a viable option for Nigeria's macroeconomic stability. It advises that the populace be informed about the complexities of redenomination beforehand, and that redenomination be implemented with the least amount of uncertainty and instability possible.